Investigating Transparency in Software Ecosystems - Zacarias, Rodrigo Oliveira; Gonçalves, Rodrigo Feitosa; Santos, Rodrigo Pereira dos (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2023)
Software Ecosystems (SECO) are a set of actors interacting with a distributed market centered on a technology platform to develop products and services. In this context, transparency is a concept that allows third-party developers to learn processes and elements that integrate the platform of SECO. This non-functional requirement impacts the coordination of developers and the management of requirements that emerge in SECO. Although it is an essential requirement, there is still a lack of a roadmap on what constitutes transparency in SECO. Thus, this study aims to investigate and characterize transparency in SECO. After investigating the literature, we selected 23 studies to analyze the state-of-the-art about transparency in SECO. Concerning the results, we could have a comprehensive view of solutions, conditioning factors, processes, and challenges related to transparency in SECO, whose discussion is centered on three main topics: access to information, communication channels, and requirements engineering. Regarding implications for academia and industry, researchers can find an overview of what has been studied so far about transparency in the SECO context, and practitioners can find solutions and conditioning factors that help them to adopt initiatives to contribute to the open flow of information in a SECO and, thus, attract and engage new actors to a technology platform.